2020
DOI: 10.1101/2020.08.13.250076
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In SilicoDesign of siRNAs Targeting Existing and Future Respiratory Viruses with VirusSi

Abstract: The COVID-19 pandemic has exposed global inadequacies in therapeutic options against both the COVID-19-causing SARS-CoV-2 virus and other newly emerged respiratory viruses. In this study, we present the VirusSi computational pipeline, which facilitates the rational design of siRNAs to target existing and future respiratory viruses. Mode A of VirusSi designs siRNAs against an existing virus, incorporating considerations on siRNA properties, off-target effects, viral RNA structure and viral mutations. It designs… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…During in silico prediction, many siRNAs were found to fulfill the less favorable criteria targeting a region in the ORF1ab gene of MERS-CoV. By using strong selection criteria and a stringent strategy, we have selected and filtered out a total of twenty-one functional, off-target siRNAs that were shortlisted from four hundred and sixty-two siRNAs as per the guidelines and basic rules of filtration [ 18 , 35 , 36 , 39 , 40 ]. The designed siRNAs’ length, nucleotide content and specificity and absence of off-target effects and secondary structures in the target site were taken into consideration by the used software during the design and filtering of the siRNAs as this would influence the efficiency, precision, and functionality of siRNAs, hence leading to a better silencing outcome [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During in silico prediction, many siRNAs were found to fulfill the less favorable criteria targeting a region in the ORF1ab gene of MERS-CoV. By using strong selection criteria and a stringent strategy, we have selected and filtered out a total of twenty-one functional, off-target siRNAs that were shortlisted from four hundred and sixty-two siRNAs as per the guidelines and basic rules of filtration [ 18 , 35 , 36 , 39 , 40 ]. The designed siRNAs’ length, nucleotide content and specificity and absence of off-target effects and secondary structures in the target site were taken into consideration by the used software during the design and filtering of the siRNAs as this would influence the efficiency, precision, and functionality of siRNAs, hence leading to a better silencing outcome [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other structure-based approaches use the ability of small molecules to target specific RNA structures or recognize and bind to RNA targets based on their secondary or tertiary structures [ 24 , 33 , 34 ]. Recently, in silico designing of siRNAs against respiratory viruses has been reported [ 18 , 35 , 36 ] including evaluation of siRNAs against MERS-CoV. We have previously performed in silico prediction alongside a pilot study for investigating the antiviral activity for 10 of the described siRNAs in a different cell culture system [ 30 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond nucleic acid diagnostics, finding maximally active and taxon-specific sequences in viral genomes has other uses that fit into ADAPT’s framework. For example, sequence diversity impacts the efficacy of sequence-based siRNAs 55 and antibody therapeutics 56 . CRISPR-based antiviral development also requires consideration of sequence diversity, guide activity, and specificity 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Beyond viral diagnostics, our approach can benefit other efforts that require designing maximally active sequences from viral genome data. For example, genomic variation impacts the efficacy of sequence-based siRNA 64 and antibody 65 therapeutics. CRISPR-based antiviral development also requires deep consideration of sequence diversity, guide activity, and taxon-specificity 66 .…”
Section: Discussionmentioning
confidence: 99%
“…This revealed that four siRNAs (3329i, 1878i, 1104i, and 2351i) were able to decrease the expression of the S gene, and four other siRNAs (418i, 881i, 214i, and 1068i) could separately reduce the expression of the N gene, while the remaining three siRNAs (607i, 344i, and 79i) could decrease the M gene expression [ 104 ]. Several researchers have also predicted functional and potential siRNAs as therapeutics using in silico analysis [ 105 , 106 ] ( Table 1 ).…”
Section: Sirna Therapy—a Potential and Promising Antiviral Therapeuticmentioning
confidence: 99%